SORRY, BUT...: PLATFORM APOLOGIES, ABUSE, AND CONSTRUCTING THE CULPABLE SUBJECT - Cross, Katherine Alejandra Angel; Hoffmann, Anna Lauren (AoIR Selected Papers of Internet Research, 2021)
Apologies have become a prominent feature of online platforms’ corporate communications. Whether in response to instances of harassment, security lapses, or political manipulation, official expressions of remorse or regret—often coupled with vows to “do better”—work to reconcile or recover a platform’s commitments in the face of public relations, economic, or regulatory pressure. Despite their prominence, however, apologies have received comparably less critical attention in research on harassment and abuse than other corporate responses. In this work, we employ discourse analysis to explore three high-profile apologies: former Reddit CEO Ellen Pao’s July 2015 apology for missteps in addressing the site’s abusive climate; Riot Games’ 2018 apology for hostility and sexual harassment at the company; and Twitch’s June 2020 apology in response to allegations that some streamers had engaged in offline sexual harassment--leading to online harassment of the alleged victims. Throughout our analysis, we pay particular attention to how apologies 1) construct and reproduce particular ideals of platforms and attendant actors and 2) distribute or assign culpability for harassment and abuse. What emerges is an outline of how this genre of corporate apology is emblematic individualist approach to structural problems like online harassment, while offering pseudo-empowerment to end users through new online "tools" that $2 are primarily responsible for using.